Distance-Based Stable Routing Decision Scheme in Urban Vehicular Ad Hoc Networks - Sang-woo Chang; Sang-sun Lee (International Journal of Distributed Sensor Networks)
A number of ad hoc routing protocols of vehicular ad hoc network (VANET) have been proposed and evaluated based on mobile ad hoc network (MANET) routing protocols. Although a large number of routing protocols have been developed in MANET, the VANET has different environments such as highly dynamic topology, frequently disconnected network, hard delay constraints for safety-related application, and various communications environments (e.g., highway or urban traffic scenarios). Therefore, development of a suitable routing protocol that considers these characteristics of VANET should be needed. In this paper we suggest the improved distance-based VANET routing protocol compared with the previous researches on urban traffic environments. We apply approaches to packet-collisions avoidance scheme in the intersection and to stable route decision scheme based on the adaptive waiting time. The performance is then evaluated under simulation which is implemented with the Manhattan urban traffic model. The results show the improved performance as compared with the previous researches.